Sociohistorical Analysis of Normative Standards of Masculinity in the Pandemic of COVID-19: Impacts on Men’s Health/Mental Health - de Sousa, Anderson Reis; Moreira, Wanderson Carneiro; da Silva Santana, Thiago; Araújo, Isabella Félix Meira; Borges, Cléa Conceição Leal; Almeida, Éric Santos; das Mercês, Magno Conceição; da Silva, Richardson Augusto Rosendo; Teixeira, Jules Ramon Brito; Lourenção, Luciano Garcia; Gomes, Nadirlene Pereira; de Santana Carvalho, Evanilda Souza; et al. (Frontiers in Psychology, 2022)
Objective This study aims to analyze sociohistorically how the normative patterns of hegemonic masculinity produced impacts on men’s health/mental health in the context of the COVID-19 pandemic. Methods A qualitative study from a socio-historical perspective was conducted with 50 men based on an online survey. A semistructured form was applied. The data were analyzed by the Collective Subject Discourse method, interpreted in the light of the context of epidemic disease and hegemonic masculinity. Results The experience of the pandemic exposed the normative patterns of masculinities from the consummation of acts representative of the pandemic context, which incited men to deny the existence of COVID-19 disease and to delay the understanding and adoption of measures to protect and control COVID-19. As a repercussion, men presented conflicts in the regulation of emotions; presented emotional suppression; were more reactive; felt threatened regarding the loss of the role of family provider, virility; and revealed a sense of invulnerability, added to the weakening of self-care. Conclusion The discourse revealed that the men’s behaviors are consistent with the characteristics of hegemonic masculinity, but express signs of recognition that this behavior causes harm to themselves and their health.